Les gravures des livres imprimés au XVIIIe siècle au Monastère-Saint-Jean-Baptiste à Khenchara – Mont Liban - Nassif, Charbel (Collectanea Christiana orientalia, 2024)
This article aims to present the books of the printing press founded by the Aleppian ʿAbd Allāh Zāḫir (1684-1748) at the Saint John the Baptist Monastery in Khenchara (Mount Lebanon) in the 18th century, the motherhouse of the Choueirite Basilian Order. The Khenchara printing press stands out as one of the most important in the 18th century in the Middle East, playing a crucial role in the spread of Catholicism while making a significant contribution to the enrichment of the Melkite Greek Church through the printing of liturgical works. Its artistic heritage is remarkable, blending iconographic motifs from the Byzantine tradition with Western motifs, thus illustrating the cultural and religious diversity that characterizes the Melkite environment.